Spinco System AA Computing Integrator for Amino Acid Analysis (1980)
Beckman's AA Amino Acid Analysis systems debuted in 1985.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Amino acids--Analysis; Integrators; Beckman Instruments, Inc.